Metodologi Penelitian Hadis Murni Dan Terapan - Asep Tatang Suryana; Tajul Arifin (Yayasan Cendekia Gagayunan Indonesia, 2024)
This study is motivated by the fact that the methodology of hadith research encompasses two primary approaches, namely pure and applied hadith studies, which play a significant role in the development of hadith studies. This research aims to analyze the definitions, objectives, procedures, similarities, differences, and examples of application of pure and applied hadith research methodologies. This study employs a normative approach and descriptive-analytical method. Data were collected using document studies from primary sources, such as hadith compilations, and secondary sources, such as hadith methodology literature. The data were analyzed using qualitative data analysis techniques. The results of this study indicate that pure hadith research focuses on the authenticity of the sanad and matan, whereas applied hadith research emphasizes its relevance and application in contemporary life. The findings of this research imply the necessity of integrating both approaches to preserve the authenticity of hadith while ensuring its relevance to the needs of the Muslim community.